Investigating the behavior of an expansive soil slope in critical linear infrastructure in China using multi-temporal InSAR - Jiang, Zhen; Wu, Zigui; Li, Ziyuan; Hu, Jun; Wu, Yuwei; Ou, Liye; Zhang, Tongyuan (Frontiers in Environmental Science, 2023)
One of the most significant pieces of linear infrastructure in China is the Middle Route of the South-to-North Water Diversion Project (MR-SNWDP), a large section of which consists of an expansive soil slope (ESS) that threatens the safety of the canal. Here, we prepared 144 Sentinel-1 data from May 2017 to July 2022 to study the behavior of the ESS in the canal section in Huixian City in the MR-SNWDP. Then, the Elastoplastic Deformation model under Wetting and Heating Effects (EDWHE) was employed to accurately characterize the displacement of the ESS. The InSAR results illustrate that the unstable zones tend to be small and are distributed along the canal slope, with the magnitude of deformations generally no more than 20 mm/year. Additionally, their deformation time series generally accumulate exponentially and evolve in a significant pattern of seasonal swelling and shrinkage. We observed that the slope movements significantly accelerated during the period when extreme rainfall occurred around 22 July 2021. Affected by satellite imagery and the geometric structure of the slope, the magnitudes and evolving trends of LOS deformation vary with different aspects of the slope sections. Then, the elastic swelling-shrinkage deformations were derived through the EDWHE model, of which the uplift or settlement was mainly dependent on geological and meteorological conditions. Moreover, the active zone depths of the ESS were retrieved using an InSAR-based lag-time approach and clearly reflected their distribution pattern. In this investigation, the behavior of the ESS in the study area was quantitatively analyzed using InSAR, and the results provide support for designing protective slope treatments and keeping the canal safe in the MR-SNWDP.